CNFET-based design ternary logic design and arithmetic circuit simulation using HSPICE - Ee, Poey Guan (2015)
This project report focuses on the multiple-value logic (MVL) or commonly known as ternary logic gates by using carbon nanotube (CNT) FETs devices (CNTFETs). It is shown ternary logic has promising future in CNTFETs when compare to conventional binary logic design, due to its simplicity and energy efficiency in digital design reduced circuit overhead such as chip area and interconnection. In this research, existing CNTFET-based binary inverter and standard ternary inverter with resistive-load (STI-R) for comparison with the other three types of inverter are proposed - Complementary Standard Ternary Inverter (CSTI); Standard Ternary Inverter with 1 resistor and 3 NCNTFET (NSTI-R); Standard Ternary Inverter with 1 resistor and 3 PCNTFET (PSTI-R) to analysis the performance, structure design and application. In addition, the research covers all the basic logic Ternary NAND gate and Ternary NOR gate for further benchmarking. All simulation results using SPICE are obtained and analyzed in the Direct Current (DC) setting and verifed using half adder. Further study behavior of ternary logic includes the implementation of partial binary design into the ternary design and performance benchmarking. The result shows the CSTI have advantage on low power design with low leakage while NSTI-R has advantage on high-speed design inverter. In addition, partial binary design in the arithmetic circuit ternary design with CSTI shows added advantage in a low power design.